PWE-431 Training our trainees: the north west deanery model. (22nd June 2015) - White, KL; Gashau, WJ; Shuttleworth, EE; Shields, P; Summerton, C
Abstract : Introduction: The North West Deanery has always had a strong educational ethos (until recently offering a Gastroenterology MSc to all trainees). We aimed to review the current ways in which our trainees are educated and supported. Method: A review of the educational events and support systems in place for our trainees from February 2014 to February 2015 was performed. Results: Trainees attend monthly training days. Content is matched to the national GI training curriculum, with a specific theme in each academic year (e.g. small bowel and nutrition). Expert speakers are local and national. A two-day regional GI Conference is organised annually and has now been running for 12 years. In July 2014, this was attended by 21 consultants and 35 trainees and followed the year's theme of upper gastrointestinal disease. Trainees presented abstracts in poster (12) and oral (10) format. Feedback scores for all speakers was a mean of 4.5/5 for interest and 4.5/5 for relevance. Feedback for all other aspects of the event was 4–5/5 and 100% of responders would attend the conference again. The trainees benefit from an annual 'Enhancing your training' event, which was introduced to give trainees guidance in the opportunities available to them outwith the training programme. The topics covered include the process for going out of programme, clinical fellowships, basic and clinical research and preparing for the transition to consultancy. We conduct an annual survey of trainees. In 2014, this was performed online and response rates were improved by 50% compared to the 2013 paper format. In the 2014 survey, endoscopy training received positive feedback with 78% trainees rating supervision level as good or excellent, 96% felt the case mix was reasonable or good and 85% felt the balance between service and training was reasonable or good. 100% had access to JETs. However 30% of trainees felt that opportunities to manage patients with gastrointestinal bleeding were poor or deficient. The annual survey results are collated and fed back to the Specialty Training Committee at their bi-annual meeting by the trainee representatives. In 2012 a mentorship programme was set up for the trainees. All new trainees are given the option of being matched to a mentor who is ST5 or later in their training. The 2014 trainee survey showed that 46% of the respondents had a mentor. Conclusion: We feel the North West Deanery provides a successful model for support and education of Gastroenterology trainees. Disclosure of interest: None Declared.